(untitled) (University Journal of Zoology, Rajshahi University, 2012)
The effect of different doses of Trichosanthes palmata (Makal) seed extract, viz. 1000, 2000, 4000, 8000 and 16000 ppm on the growth and development of Tribolium castaneum and T. confusum was assessed. All the treatments significantly reduced the weight of T. castaneum and T. confusum. Treatments significantly lengthened the larval and pupal periods of both the species. Significantly lower pupal recovery and adult emergence were also observed. DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10735 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 17-20